Tinjauan Penggunaan Sistem Informasi Akademik Case Study: Perguruan Tinggi XYZ - Niska Ramadani; Fadlul Amdhi Yul; Ismail Arifin (Universitas Putra Indonesia YPTK Padang, 2024)
Academic information system is an information and communication technology that processes and integrates all information and academic administration in higher education, so that it can manage data effectively, efficiently, and integrated. Users hope that the academic information system can provide convenience starting from data processing, registration processes, scheduling lectures, managing grades, and monitoring student attendance. Universities must provide services with technology continuously, academic information systems are expected to have high availability and reliability, in order to be able to provide services to users, this is also one of the key functions in the success of the academic service process. In the strategic plan for information technology development, XYZ College will improve services in the academic information system, so as to provide service satisfaction and a better experience. This study aims to evaluate the availability and reliability of the use of academic information systems that will be used as a basis for making long-term strategic plans for the development of college information technology, and operational plans in information technology. Evaluation of availability and reliability is done by measuring the level of user satisfaction in using the academic information system at XYZ College. Measurements are made by looking at user perceptions through indicators of system quality, information quality, perceived usefulness, perceived ease of use, service quality, user satisfaction and net benefits. The evaluation results are then aligned with the Availability and reliability of the system in order to further determine the level of functionality of the current system availability. Based on the results of the analysis, the current condition can be clarified. The results showed that of the 11 hypothesized relationship paths proposed, 5 were rejected and 8 were accepted. Where the quality of information, ease of use, and usefulness of the system do not affect SIADAK user intentions, then service quality and system quality have a positive effect on user intentions to access the academic information system, the variable that has the highest relative influence value is service quality, because service quality can affect user satisfaction directly.